Does protection policy actually produce equality among labours? A tentative rules approach to the answers protective problems migrant labour : case migrant labours from East Java, Indonesia - Anita Kristina (Neo-Bis, 2017)
Purpose - The purpose of this paper is to analysis effectiveness of the protective rule and their practical effects.Design/approach - This paper reviews the most important tentative rules and focusing on the principal agent model, which considers the functioning insurance policy to give equality protection. The research has a crucial to analyses the current mechanism of protection policy of cause for disfunction of rules, it actually causes the most orientation to be assumed by labour migran as a principal and the subject of the protection policy. Case study in East Java, Indonesia.Findings – This mechanism appears theoretically coherent with the protection policy, of equality among labour migran with their performances, but this effect is baced on the benefits of their future performance; this is happened only within their state that their work. The paper concludes that the best effective protection for the labour migran who be a strong protection of the strong coordination actors or the harmonization concepts – by a system of information, professional procedure, capable of reducing as much rules, either pre-existing of the design protection policy.Value – The paper offers insight into the issue of whether rules protection actually produce equality among migrant labour.